The roles of parenting patterns in shaping the religious character of students at SMPN 9 Palu - Sasmita, Tri; Silalahi, Micha Felayati; Wahyuningsih Riyadi, Nur Eka; Diniy, Muh Yusran (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to describe parental parenting styles in shaping children’s religious character and to examine differences in students’ religious character based on the parenting styles applied at SMP Negeri 9 Palu. The study is grounded in the phenomenon that students’ religious character development varies widely, while each family adopts different parenting patterns that may influence the habituation of religious values. Early adolescents also face social dynamics and technological influences, which require consistent parental guidance. This research employs a quantitative approach with a questionnaire as the primary instrument, supported by observations and interviews to enrich understanding and validate quantitative findings. The sample was determined using the Slovin formula with a 5% margin of error, resulting in 258 student respondents. Data were analyzed using a One-Way ANOVA to identify differences in religious character among students raised under democratic, authoritarian, and permissive parenting styles. The findings show that the democratic parenting style is the most frequently applied, and students’ religious character generally falls into the “good” category. An F-value of 4,591 with a significance level of 0,003 (<0,05) indicates significant differences in religious character across parenting styles. These results emphasize that parenting characterized by communication, exemplary behavior, and supervision plays an important role in shaping children’s religious character.